Geographic distribution of federal funds in New Mexico - United States. Executive Office of the President; United States. Community Services Administration; United States. Community Services Administration. Office of the Controller ([Silver Spring, Md. : Office of the Controller, Community Services Administration ; Springfield, Va. : National Technical Information Service, distributor, 1977)
Includes data for the executive branch of the federal government only.
Description based on: 1980.
Report covers fiscal year.
Available in microfiche.
National and state level data also contained in: Geographic distribution of federal funds in summary, ISSN 0162-1734.
Keywords: Economic assistance, Domestic -- New Mexico -- Statistics -- Periodicals